1981
DOI: 10.1002/1097-0142(19810215)47:4<780::aid-cncr2820470424>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Lauren and Ming classifications and other pathologic parameters in gastric carcinoma

Abstract: One hundred seventy-two patients with gastric carcinoma were studied (111 men and 61 women). Mean age was 54.0 +/- 11.2 years, and the overall five-year survival rate was 37.5%. There were four carcinomas in situ and one double carcinoma; the remaining 167 were classified as intestinal (112), diffuse (48), and atypical (7), according to Lauren; and as expanding (96) and infiltrative (71), according to Ming. Both classifications had prognostic significance; that of Lauren's could not be ascribed to sex and age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
63
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 8 publications
6
63
0
Order By: Relevance
“…Furthermore, we biologically interpreted each profile in search of insights into the molecular mechanisms underlying the type's behavior. Special emphasis was placed on the diffuse type, because it is explicitly more invasive and aggressive than the intestinal one, resulting in poorer prognosis for affected patients, 15,16 and is of increasing incidence worldwide. 17,18 Novel insights regarding its molecular background and behavior may lead to a more effective, entity-specific treatment.…”
mentioning
confidence: 99%
“…Furthermore, we biologically interpreted each profile in search of insights into the molecular mechanisms underlying the type's behavior. Special emphasis was placed on the diffuse type, because it is explicitly more invasive and aggressive than the intestinal one, resulting in poorer prognosis for affected patients, 15,16 and is of increasing incidence worldwide. 17,18 Novel insights regarding its molecular background and behavior may lead to a more effective, entity-specific treatment.…”
mentioning
confidence: 99%
“…However, follow-up studies on the prognostic value of these indexes in patients with cardia adenocarcinoma have provided conflicting results (Ribeiro et al, 1981;Husemann, 1989;Maehara et al, 1991;Jakl et al, 1995;Ohno et al, 1995;Kajiyama et al, 1997;Caldas et al, 1999;Pinheiro et al, 1999). As a consequence, new classification systems have been suggested as prognostic factors.…”
mentioning
confidence: 99%
“…It has also been reported that patients with diffuse gastric carcinoma are younger than those with the intestinal-type (Lauren, 1965;Noda et al, 1980;Ribeiro et al, 1981;Hanai et al, 1982;Mecklin et al, 1988). Two studies are concordant that this difference is in the order of 7-8 years (Lauren, 1965;Ribeiro et al, 1981).…”
mentioning
confidence: 95%
“…Accordingly, it is recommended that resections should be more extensive in patients with this tumour than in patients with the intestinaltype tumour (Gall & Hermanek 1985, Heberer et al, 1988. It is well documented that the prognosis for the diffuse carcinoma is poorer than for the intestinal-type carcinoma (Lauren, 1965;Stemmermann & Brown, 1974;Ribeiro et al, 1981; Hermanek, 1986;Viste et al, 1986).It has also been reported that patients with diffuse gastric carcinoma are younger than those with the intestinal-type (Lauren, 1965;Noda et al, 1980;Ribeiro et al, 1981;Hanai et al, 1982;Mecklin et al, 1988). Two studies are concordant that this difference is in the order of 7-8 years (Lauren, 1965;Ribeiro et al, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation